Strategy and structure of the hotel industry in Malaysia / Salleh Mohd Radzi ... [et al.] - Mohd Radzi, Salleh; Amran, Mohamed; Aziz, Abdul Razak; Supardi, Azlan (Institute of Research, Development and Commercialization (IRDC), 2007)
The major purpose ofthis study was to examine the relationship of strategy and structure. Porter s(/980) strategic typology was utilized to classify hotel firms by strategic orientation; and, an analysis of variance was performed to determine the differences in their performance. Structural Equation Modeling was used to confirm the factors underlying the strategy and structure constructs.